A role of noradrenergic receptors in anxiolytic-like effect of high CRF in the rat frontal cortex. (August 2021) - Śmiałowska, Maria; Zięba, Barbara; Domin, Helena
Abstract: Corticotropin releasing factor (CRF) is a neuropeptide widely distributed in the brain as a hormonal modulator and neurotransmitter. The best known behavioral function of CRF is activation of stress and anxiety via the hypothalamus and limbic structures but the role of CRF in the cortex is still poorly understood. Our previous studies have shown anxiolytic-like effects of high doses of CRF injected into the Fr2 frontal cortex and involvement of CRF1 receptors (R) in that effect. These results seemed to be controversial as most other studies suggested anxiogenic and not anxiolytic effects of CRF1R stimulation. Since stress is associated with adrenergic system, in the present study, we focused on participation of alpha1 and alpha2 or beta adrenergic receptors in the anxiolytic-like effect of CRF. Moreover, we verified whether these effects of CRF in the Fr2 were really connected with CRF1R. Male Wistar rats were bilaterally microinjected with CRF in a dose of 0.2 μg/1 μl/site or with the specific agonist of CRF1R, stressin 1 (0.2–0.0125 μg/1 μl/site) into the Fr2 area. The elevated plus maze (EPM) test was performed 30 min later to assess the anxiolysis. An involvement of noradrenergic receptors in the CRF induced anxiolytic-like effect in the Fr2 was studied by pretreatment with the alpha1 antagonist prazosin, alpha2 agonist clonidine, alpha2 antagonist RS 79948 or beta antagonist propranolol, 20–30 min before CRF. The influence on anxiety was assessed in the EPM test. The results show that anxiolytic behavior after CRF microinjection into the Fr2 area seems to be mainly connected with the CRF1R activation because a similar effect was observed after stressin 1 administration and it was blocked by CRF1R antagonist. The results observed after administration of noradrenergic ligands indicated that anxiolytic effects of CRF in the Fr2 engaged the alpha1 and alpha2 adrenergic receptors but not beta receptors.